Operational impact estimation of container inspections at Dalian Port: the application of simulation. (February 2017) - Wang, Wenyuan; Zhou, Yong; Song, Xiangqun; Tang, Guolei; Fang, Zexing
For the security of ports and the container shipping industry, a key problem for a container terminal is the planning and design of the inspection area. The main goal of this paper is to address an inspection investment planning problem for the international container terminal at Dalian Port using the simulation method. Considering various types of container ships and flexible container truck scheduling and routing, we propose a framework combining an Arena-based simulation model with a developed optimization procedure. Two components of this integrated framework realize information communication via the interface of Visual Basic for Applications. Under the potential inspection protocol, simulation experiments are designed and carried out for investigating the operational impact of container inspections for different allocations of inspection resources at the terminal, including the turnaround time of external trucks, the number of trucks waiting in the inspection area, etc. This paper includes the description of the conceptual framework, the detailed simulation model, the experimental design, and the simulation results.